Challenges, Adaptation, and Impacts: A Comprehensive Study of BSI Laku Pandai Agents in Providing Islamic Financial Services in Remote Areas - Daus, faizal; Oktaviani, Yeni (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2025)
This study examines the implementation of the BSI Laku Pandai program as an instrument of Islamic financial inclusion in remote areas, focusing on Bang Haji, Pagar Jati, and Merigi Sakti sub-districts in Central Bengkulu Regency. The main objectives are to identify the challenges faced by agents, analyze their adaptive strategies, and assess the program’s impacts on the economic and social well-being of local communities. The research employs a qualitative approach through in-depth interviews, observations, and document analysis, guided by Amartya Sen’s Capability Approach. The findings reveal that agents face structural barriers, including poor infrastructure, low financial literacy, and limited operational capacity. Nevertheless, agents developed adaptive strategies such as collaborating with religious leaders, using religious narratives, employing alternative technological solutions, and providing door-to-door services. The program has delivered tangible benefits by reducing reliance on informal moneylenders, fostering trust in formal institutions, expanding access to sharia-compliant financing for microenterprises, and reinforcing the community’s religious identity. The study concludes that financial inclusion should not be measured solely by access to services but by the extent to which such services enhance people’s substantive capabilities. Accordingly, the program requires complementary measures, including financial literacy initiatives, digital infrastructure development, and continuous capacity-building for agents, to ensure broader and more sustainable impacts.